Desire for Pregnancy and Risk Behavior in Young HIV-Positive Women - Finger, Julie L. (Mary Ann Liebert, Inc., 2012)
This cross-sectional study utilized data from 130 young women with behaviorally acquired HIV to examine the association between desire for pregnancy (DFP) and both sociodemographic variables and sexual risk behaviors. A single item was utilized to assess DFP. Bivariate and multivariate regression analyses were conducted. At the bivariate level, DFP was associated with increased rates of intercourse, decreased condom use, increased partner concurrency, increased rates of unprotected sex with a nonconcordant partner, and a higher number of previous sexually transmitted infections (STIs). Multivariate analyses suggested that DFP was associated with increased likelihood of recent intercourse, condom-unprotected sex, and oral sex. DFP was related to few sociodemographic variables but was associated with having fewer children currently, a history of victimization, and decreased rates of disclosure of HIV status. The few sociodemographic variables that were associated with DFP suggest that social relationships may play a role in DFP. DFP was associated with sexual behaviors that may place young women at risk for STI acquisition and secondary HIV transmission to partners. Health care providers should assess DFP in routine HIV care, providing education about fertility options, interventions for vertical transmission, family planning, and risk reduction counseling.